PENGARUH KUALITAS, MEREK, KEMASAN DAN HARGA PRODUK TERHADAP KEPUTUSAN PELANGGAN DALAM MEMBELI KOPI DAN BOBA DIKALANGAN REMAJA MILENIAL DI KOTA MALANG (Manajemen & Bisnis Jurnal, 2022)
This study aims to examine and analyze the effect of quality , brand, packaging, and product price on customer decisions in buying coffee and boba among millenial teenagers. Respondents as many as 200. The analytical tool used is SEM analysis . The results showed that the products quality of starbucks , kopi kenangan , xiboba , and chatime were judged to provide good product quality . Good product packaging , good taste and attractive packaging and safe drinks for consumption are the advantages of the starbucks , kopi kenangan , xiboba , and chatime, because they can leave a poitive impression on consumers so that consumers can make further purchases. Interesting and unique brand names , namely starbucks , kopi kenangan , xiboba , and chatime were considered attractive by some informants , this made the brand able to make an impression on people’s memories. In taste , everyone has different in assessing the level of enjoyment of sturbucks starbucks products , kopi kenangan , xiboba , and chatime . Attractive and unique packaging of starbucks ,kopi kenangan , xiboba , and chatime products . So that customers can make further purchases. Affordable price among customers make starbucks products , kopi kenangan , xiboba , and chatime often purchased by customers/consumers . Quality , brand , packaging , dan price have a positive and siqnificant influence on customers decisions to consume coffe and boba